Videography and public speaking training for organizing webinars for Multimedia Schools in Surakarta - Haryo Kusumo Aji; Herning Suryo Sardjono; Sihabuddin Sihabuddin (Universitas Muhammadiyah Magelang, 2022)
The pandemic of Covid-19 has rendered normal activities impossible. Similarly, face-to-face seminars are no longer possible and are being replaced by webinars. However, there were numerous technical issues that disrupted the webinar's operation, causing the message to be miscommunicated to the participants. As a result, through videography and public speaking training, this program aims to introduce the technicalities of organizing webinars. The program takes the form of providing the basis and theory for how to put together a good webinar and use multi-camera tools. As a result of this program, 25 students from SMK Kristen 1 Surakarta gained a better understanding of webinar implementation and were able to create webinars on their own.